Improving the Thermosphere Ionosphere in a Whole Atmosphere Model by Assimilating GOLD Disk Temperatures. Issue 3 (9th March 2022) - Laskar, F. I.; Pedatella, N. M.; Codrescu, M. V.; Eastes, R. W.; McClintock, W. E.
Abstract: Global‐Scale Observations of Limb and Disk (GOLD) disk measurements of far ultraviolet molecular nitrogen band emissions are used to retrieve column integrated disk temperatures (Tdisk ), which are representative of the lower‐and‐middle thermosphere. The present work develops a new approach to assimilate the Tdisk in the whole atmosphere community climate model with thermosphere‐ionosphere eXtension using the data assimilation research testbed ensemble adjustment Kalman filter. Nine days of data, 1–9 November 2018, are assimilated. Analysis state variables such as thermospheric effective temperature (Teff, airglow layer integrated temperature), ratio of atomic oxygen to molecular nitrogen column densities (O/N2 ), and column electron content are compared with a control simulation that is only constrained up to ∼50 km. It is observed that assimilation of the GOLD Tdisk improves the analysis states when compared with the control simulation. The analysis and model states, particularly, Teff, O/N2, and electron column density (ECD) are compared with their measurement counterparts for a validation of the assimilation. Teff and O/N2 are compared with GOLD Tdisk and O/N2 . While, the ECD is compared with ground based total electron content measurements from global navigational satellite system receivers. Root mean square error (RMSE) improvements in Teff and O/N2 are about 10.8% and 22.6%, respectively. The RMSE improvement in analyses ECD is about 10% compared to the control simulation. Plain Language Summary: Understanding the temperature and density variability of the thermosphere‐ionosphere system is very important for satellite drag calculations and satellite communication. The thermosphere‐ionosphere system is influenced by waves from the lower atmosphere and solar and geomagnetic forcing from above. For the characterization of this coupled system, realistic whole atmosphere ionosphere parameters are of great interest. The global‐scale observations of limb and disk (GOLD) satellite mission provides daytime thermospheric temperature observations with unprecedented local time and spatial coverage. Including them with the lower and middle atmospheric observations in a whole atmosphere data assimilation system, we find that they improve the state of the thermosphere‐ionosphere. This shows the promise of the GOLD disk temperatures in improving thermosphere‐ionosphere states and their potential use to improve space weather forecast capabilities. Key Points: A new approach has been developed to assimilate Global‐Scale Observations of Limb and Disk (GOLD) Tdisk in whole atmosphere community climate model with thermosphere‐ionosphere eXtensions which is validated using independent measurements Analysis states of both the thermosphere and ionosphere show improved agreement with independent measurements Results demonstrate a great potential of the GOLD Tdisk data to improve thermosphere‐ionosphere data assimilation